CYP3A drug metabolism in the developmental age: recent advances - Nowak, Jan Krzysztof; Bancerz, Bartłomiej; Bartkowska-Śniatkowska, Alicja (Journal of Medical Science, 2019)
Background. The 3A subfamily of cytochrome P450 (CYP3A) accomplishes phase I metabolism for approximately half of the available medications. We aimed to review the recent advances in our understanding of CYP3A activity, which could apply to infants and toddlers. Material and Methods. A literature review. Results. The reviewed recent data cover: CYP3A7 expression and functions, changes of CYP3A4 function in the first two years of life, CYP3A intestinal metabolism and zonation, CYP3A metabolic programming, pediatric CYP3A pharmacogenetics, the impact of critical illness on CYP3A, phenotyping, and other clinical implications of a better comprehension of CYP3A biology. Conclusions. Although the knowledge of CYP3A enzymes has already changed pediatric practice, much more is to be expected in the upcoming years. The areas to watch include: endogenous markers for phenotyping, new CYP3A7 substrates and products, pharmacogenetic interactions with transporter genes for non‑immunomodulatory drugs, as well as interactions with microbiota and specific bioactive foodstuffs.